Motivational Leadership Practices of Site Engineers in Managing Construction Labour in the Global South : A Qualitative Study From Nepal - Adhikari, Namaraj (My University, 2026)
In the context of Global south countries like Nepal, Construction industry has been a very crucial in terms of the development process, also the practices of the motivational leadership in these area are under investigated empirically. The nature of construction sites in Nepal is characterized by informal labour arrangements, high physical job demands, resource constraints, and culturally specific workplace dynamics that differ significantly from the formal organizational settings wherein mainstream leadership theories have been developed and tested. This paper explores the ways in which site engineers can encourage the labour force in the construction sector through relational, supportive and equity based leadership practices and the contextual challenges which inform their ability to do so. The research design adopted was a qualitative research design involving semi structured interviews with eight site engineers involved in ongoing constructions in Tanahun, Pokhara, and Kathmandu, Nepal. Some of the projects were hydropower development, road construction, commercial building, and residential construction. The thematic analysis approach was used to analyse data based on an integrated theoretical framework of Leader Member Exchange (LMX) theory, Job Demands Resources (JD R) model, and Social Exchange Theory (SET). There were three themes, which were identified to be overarching. First, relational leadership and trust building turned out to be the most basic aspect of motivational leadership supported by LMX theory. Second, fairness, recognition and reciprocity were also identified to be fundamental in maintaining worker motivation supported by Social Exchange Theory. Third, site engineers proactively handled the balance between high job demands and the provision of resources, such as safety equipment, practical guidance, welfare support, and supervisory presence serving as demand buffer in line with the JD R model. The research provides empirically based, context savvy knowledge on leadership and motivation in the Global South construction contexts, which extends the existing theoretical frameworks and provides practical advice to the site engineers, construction organisations and policymakers in Nepal and possibly in similar developing economy settings.
Keywords: construction industry; motivational leadership; Strategic Project Management; Master’s Programme in Industrial Engineering and Management